Common salt is better than clobetasol propionate in the treatment of umbilical granuloma. - Abdoufatouh, F.; Mesbah, B.E.; Ebrahem, M.; Omran, A.; Khashana, A. (European Journal of Pediatric Dermatology, 2021)
Background. Umbilical granuloma is the most common umbilical problem in neonates. Although many care modalities exist for umbilical granuloma like chemical cauterization, cryocauterization, electrocauterization, granuloma ligation and surgical excision, each technique has its benefits and weaknesses. In this condition, common salt is an appropriate tool for the management of umbilical granuloma. Methods. This is a randomized and controlled study on 50 children with umbilical granuloma divided into two groups (group A treated with table salt and group B treated with clobetasol propionate) and aimed at evaluating the effect of salt with respect to clobetasol. Results. After one week of treatment the recovery percentage in group A was significant-ly higher than in group B (98.80±4.4 versus 70.4±33.1, p<0.001) and after three weeks there was non-significant difference in the recovery percentage between group A & B (100.0±0.0 versus 92.0±27.7, p=0.15). Conclusion. Treatment of umbilical granuloma with table salt is a simple, effective and inexpensive form of treatment without complications.